Síntesis de ceolitas a partir de arcillas caolínicas - Marfil, Silvina Andrea (1992)
Sinthesis experiments have been carried out in order to obtain zeolites form kaolinics clays. The method consisted in a treatment of kaolins (either naturals or thermically treatest at 600 and 1000 °C), with sodium and potassium hidroxide at 80°C. The reaction products were studied by XRD. After 32 days with a NaOH solution 1 N, the natural and both heated kaolinites gave Zh zeolite (ASTM 16-612) as reaction product. Besides, with the former it was also obtain a ZK zeolite (ASTM 18-1198) and with the 600°C heated kaolinite a Na-A zeolite (ASTM 11-590). In a second stage the sinthesized zeolites were treated with a KOH solution 1 N for 32 days. Only the zeolite formed from natural kaolinite reacted giving a zeolite phase N. With the KOH 1 N solution the 1000 °C heated kaolinite rerained unchange and the 600°C heated one gave a zeolite phase N. The natural kaolinite changed first (32 days) to a potassium chabacite (ASTM 12-194) and later (75 days) to a sodalite phase N (ASTM 23-1313). In the second stage, with the NaOH 1 N solution only K-chabacite obtained from the natural kaolinite changed to a Na sodalite (ASTM 20-1070). Others remained unchange.